The politics of fish marketing in the major public markets in Iloilo City - Champlon, Ma. Edzelle M
This is a descriptive study on the politics of fish marketing in the major public markets in the Iloilo City. This study was conducted in the four major public markets in Iloilo City (Iloilo Central Market Terminal Market, Jaro "Big" Market and Lapaz Public Market), using interviews with respondents, key informants and secondary data taken from the records of the Department of Trade and Industry (DTI), City Treasurer's Office (CTO), National Statistical and Coordination Board (NSCB) and Philippine Fish Marketing Authority (PFMA). The following are the results of the study: 1) Fish Marketing in the wholesale and the retail market is an arena of power struggle among fish marketing actors - producer, brocker, wholesaler, wholesaler-retailer, retailer and consumer; 2) The fish producer has the control over the supply of fish the broker has the power over the marketing flow and selling prize of fish; 3) the suki system does not ensure consumer that she/he is free from the unfair sales of the fish traders; 4) The presence of so many fish marketing intermediaries between the producer and the ultimate buyers had resulted to fish supply insecurity in Iloilo City due to the towering of prices of fish and also to the diminish degree of fish as it reaches the ultimate buyer; 5) the government lacks proper and regular monitoring on how fish are marketed, which resulted to an unorganized fish marketing in Iloilo City. Power struggle between fish marketing actors in terms of who control the marketing flow, supply and selling price of fish, and lack of proper and regular monitoring of the government on how fish are marketed had apparent bearing on food security in Iloilo City.